Metallothionein in human thrombocyte precursors, CD61+ megakaryocytes - Rahman, Mohammad Tariqur; De Ley, Marc (Springer Netherlands, 2008)
The in vitro biosynthesis of metallothionein (MT) was investigated in thrombocyte precursors (megakaryocytes) isolated from human cord blood. Biosynthesis and induction of MT in magnetic cell sorting-separated CD61(+) megakaryocytes was confirmed by immunohistochemical staining using monoclonal mouse anti-MT. The presence of MT was detected both in the nuclear and in the cytoplasmic post-treatment with 100 micromol/L of zinc supplement. Seven isoform-specific mRNAs namely, MT-1A, MT-1B, MT-1E, MT-1G, MT-1H, MT-1X, and MT-2A were detected in the similar area. Using RT-PCR, in vitro upregulation/induction of total MT transcripts was observed in CD61(+) cells at 48 h cell populations left untreated with zinc.